CURCUMIN AS A NOVEL TREATMENT FOR HEMOGLOBINOPATHIES: MECHANISMS AND EFFICACY AND CLINICAL APPLICATIONS OF CURCUMIN - Dr. Aida El Alginawi; Ch. V. Ramana Devi; Hiba Mahgoub Ali Osman; Isra Omar; Hamdan Siddig Sirag Ahmad; Gamal Eldin Mohammed Osman Elhussein (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Since ancient times, plant-based remedies and their constituents have been highly regarded for health management. Numerous studies involving animal models and clinical trials have demonstrated the beneficial effects of medicinal plants in disease control through the modulation of various biological activities (1, 2). Natural products and their derivatives have gained significant popularity in health management, with their importance documented in religious texts, including the Bible and Quran. Prophet Mohammad (Peace Be Upon Him) also recommended various plants for disease cure and prevention. In this context, turmeric (Curcuma longa) and its key component, curcumin, have been used for thousands of years in the treatment of various diseases due to their efficacy, affordability, and rich source of antioxidants (3). Toxicity studies have shown that curcumin is quite safe, even in high doses (up to 12 grams in humans) (4). Curcumin, the primary constituent of turmeric, has been proven to possess clinical therapeutic properties, with its antioxidant effects playing a vital role in managing chronic inflammatory diseases (5). Previous research has demonstrated curcumin’s therapeutic potential as an antifungal, antiviral, antioxidant, and anti-inflammatory agent, along with its ability to manage other pharmacological activities (6, 7). In this review, we summarize the therapeutic roles of curcumin in disease prevention, including cancer, diabetes, cardiovascular diseases, and other ailments, through the modulation of biological activities (8, 9, 10, 11).